1990
DOI: 10.1002/glia.440030406
|View full text |Cite
|
Sign up to set email alerts
|

Glial response to axonal injury: In vitro manifestation and implication for regeneration

Abstract: Crushed fish optic axons readily regenerate, while similarly injured rat optic axons do not; the reasons for the differences in regeneration ability may lie in differences in the environment of the axons. We have cultured glial cells from previously crushed optic nerves of fish and rat to determine whether a relationship exists between the ability to regenerate and the nature of the responses of the associated nonneuronal cells to injury. The glial cells were examined using indirect immunofluorescence with ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…We have shown in the past that CM derived from regenerating fish optic nerves can facilitate axonal growth in vivo (15,16). Independently, we showed that in vitro this preparation possesses a number of activities, including cytotoxicity to mature oligodendrocytes of both fish and rat (12)(13)(14).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…We have shown in the past that CM derived from regenerating fish optic nerves can facilitate axonal growth in vivo (15,16). Independently, we showed that in vitro this preparation possesses a number of activities, including cytotoxicity to mature oligodendrocytes of both fish and rat (12)(13)(14).…”
Section: Discussionmentioning
confidence: 79%
“…Carp (Cyprinus carpio, 800-1200 g; Tnuva, Israel) were anesthetized with 0.05% 3-aminobenzoic acid ethyl ester (Sigma), and their optic nerves were crushed with forceps (for 30 sec). Eight days later, the nerves were removed by dissection and incubated in serum-free medium for 1.5 hr (four nerve segments per 300 pLI of medium) at 250C (15). The resulting medium, defined as CM, was then collected, and its protein content was determined by the Bradford assay (17).…”
Section: Materials and Methods Preparation Of Soluble Substancesmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of laminin, a molecule supportive of neuritic outgrowth, was shown to be elevated in the fish optic nerve following injury (Hopkins et al, 1985;Liesi, 1985). The possible removal of inhibitory elements is supported by the presence of oligodendrocyte-cytotoxic molecules in the regenerating fish optic nerve Sivron et al, 1990Sivron et al, , 1991Eitan et al, 1992) and by the elevation of apolipoprotein A-I (apo-A-I) and myelin-degrading enzymes (Hare1 et al, 1989;Salles et al, 1990). It thus seems likely that the combined action of several factors is responsible for the increase in growth permissiveness of the fish optic nerve following injury.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, the structural properties and cell lineage relationship of oligodendrocytes is highly comparable between zebrafish and mammals (Jeserich et al, 2008;Jeserich and Stratmann, 1992;Jeserich and Waehneldt, 1986;Sivron et al, 1990). Also, orthologous genes for all of the major mammalian myelinassociated genes have been found in zebrafish (dm20, mbp and p 0 ) (Brosamle and Halpern, 2002).…”
Section: Zebrafish and Mammalian Myelin: A Comparisonmentioning
confidence: 99%